Onesnaženost zraka v socialistični Sloveniji – vzroki in odzivi - Rendla, Marta (Studia Historica Slovenica, 2024)
The article addresses the negative effects of economic and social development, especially the accelerated industrialization and urbanization, on the environment in socialist Slovenia. The authors studied the environmental footprint of economic and social development primarily on the basis of numerous discussions by natural scientists, chemists, geographers, and climatologists alongside the work of economic historians, geographers, and urban planners. The negative effects of development began to manifest in the 1950s and 1960s in the widespread environmental pollution, especially in the alarming air pollution. The deteriorating state of the environment triggered, on one hand, the emergence of modern environmental awareness and later the environmental movement, and on the other hand, the formation of a comparatively advanced environmental policy. The article on air pollution in socialist Slovenia represents a small but significant piece in understanding the environmental history, which has been largely overlooked in Slovenian historiography
Keywords: air pollution; environmental movement; environmental policy; industrializacija; industrialization; Jugoslavija; modern environmental awareness; moderna okoljska zavest; okoljska politika; okoljsko gibanje; onesnaženost zraka; Slovenija; socializem; urbanizacija; urbanization